ChemInform Abstract: A Mild Method for the Synthesis of a Novel Dehydrobutyrine‐Containing Amino Acid. Issue 51 (23rd December 2014) - Webster, Alexandra M.; Coxon, Christopher R.; Kenwright, Alan M.; Sandford, Graham; Cobb, Steven L.
Abstract The reaction between the amino acid ester (I) and pentafluoropyridine in the presence of potassium carbonate causes the desired elimination reaction to form the desired product.